2008
DOI: 10.1016/j.neuron.2008.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Architecture and Activity-Mediated Refinement of Axonal Projections from a Mosaic of Genetically Identified Retinal Ganglion Cells

Abstract: Our understanding of how mammalian sensory circuits are organized and develop has long been hindered by the lack of genetic markers of neurons with discrete functions. Here, we report a transgenic mouse selectively expressing GFP in a complete mosaic of transient OFF-alpha retinal ganglion cells (tOFF-alphaRGCs). This enabled us to relate the mosaic spacing, dendritic anatomy, and electrophysiology of these RGCs to their complete map of projections in the brain. We find that tOFF-alphaRGCs project exclusively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
316
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 253 publications
(331 citation statements)
references
References 64 publications
14
316
1
Order By: Relevance
“…These RGC types also terminate in ventromedial regions of dLGN, an area in which some W-like cells were located. Additionally, we found that X-like cells that showed perhaps the strongest regional preference residing almost exclusively in the ventroposterior region of dLGN just dorsal to IGL seem to represent just a small portion of much larger terminal domains for several indentified RGC types that vary both in morphology and receptive field structure (Hattar et al, 2006;Huberman et al, 2008Huberman et al, , 2009Kim et al, 2008Kim et al, , 2010Badea et al, 2009;Siegert et al, 2009;Ecker et al, 2010;Kay et al, 2011). Indeed, such overlap between RGC projections and the spatial preferences of dLGN cells is to be expected given the wide diversity of RGC types (Masland, 2001).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…These RGC types also terminate in ventromedial regions of dLGN, an area in which some W-like cells were located. Additionally, we found that X-like cells that showed perhaps the strongest regional preference residing almost exclusively in the ventroposterior region of dLGN just dorsal to IGL seem to represent just a small portion of much larger terminal domains for several indentified RGC types that vary both in morphology and receptive field structure (Hattar et al, 2006;Huberman et al, 2008Huberman et al, , 2009Kim et al, 2008Kim et al, , 2010Badea et al, 2009;Siegert et al, 2009;Ecker et al, 2010;Kay et al, 2011). Indeed, such overlap between RGC projections and the spatial preferences of dLGN cells is to be expected given the wide diversity of RGC types (Masland, 2001).…”
Section: Discussionmentioning
confidence: 72%
“…For example, we found that Y-like cells occupy a central core in dLGN, a region that serves as the primary terminal domain for transient Off-␣-cells and a group of On/Off direction-selective cells that responds to posterior motion (Huberman et al, 2008;Kim et al, 2010. These RGC types also terminate in ventromedial regions of dLGN, an area in which some W-like cells were located.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…2B, a single oligodendrocyte outlined by NG2 expression shows overlapping staining for Contactin on the cell body and on proximal but not distal processes. At P10, Contactin was undetectable on optic axons that by this time point had innervated their targets (20,21). At P16, a dramatic change in pattern occurred, with prominent Contactin staining now delineating parallel running structures resembling myelin membranes.…”
Section: Resultsmentioning
confidence: 94%
“…RGC axons enter the tectum at one of four sublaminae and remain in those layers to find and refine their topographic connections [267]. The lamina targeted by each RGC depends on the RGC subtype and intrinsic properties, although most RGCs innervate superficial laminae within the neuropil [5,90,141,142,238,362,366]. The secreted protein Slit1, expressed in a high-superficial to low-deep gradient, signals to Robo2 receptors on the RGC axons to guide axons into the correct lamina [363].…”
Section: The Tectum Is An Intricate Integrative Structurementioning
confidence: 99%